ANALISIS PERBANDINGAN PEMBIAYAAN KPR TERHADAP SUKU BUNGA KOMPETITIF FIX & CAP PADA PT. BANK CENTRAL ASIA, Tbk. - Wulandari, Oktaviana Ayu; Zannati, Rachma (Economic Faculty, Attahiriyah Islamic University, 2017)
This study aims to determine the differences and trends between home mortgage financing to competitive interest rates at PT. Bank Central Asia, Tbk. In this study, the sample used is the interest rate data in the year 2009-2016. Data collection techniques used in this study through observation and interview techniques. The analysis method used is independent t-test and trend analysis test using SPSS 20.0 for Windows program. Based on the result of research, sig-t is obtained 0,023